Efeito de multiestressores (temperatura e bisfenol A) no crescimento de duas espécies de macrófitas - Sant'Ana, Laiane Neri (Universidade Federal de São Carlos, 2026)
Freshwater ecosystems are increasingly subjected to multiple pressures, including climate change, pollution, and alterations to the hydrological cycle. This context creates a multi-stressor environment for organisms inhabiting aquatic systems, such as macrophytes, plants that occupy wetlands or fully aquatic habitats. Plant communities are directly influenced by temperature, which modulates their metabolic rates and growth parameters, and may interact synergistically with other stressors, such as chemical pollutants. Bisphenol A (BPA) is a synthetic organic compound widely used in plastic production and is an emerging contaminant that interacts with aquatic organisms, including macrophytes. The objective of this study was to evaluate the effects of bisphenol A and temperature, within a climate change context, on two macrophyte species (R. natans and S. auriculata). The following hypotheses were tested: (i) BPA would exert negative effects on plant growth and development; (ii) a 2 °C temperature increase would synergistically interact with the contaminant, potentiating its toxic effects; and (iii) R. natans and S. auriculata would exhibit similar growth responses when exposed to identical conditions. Specimens of both species were individually exposed to bisphenol A concentrations of 0 mg/L (control), 2.5 mg/L, and 10 mg/L (50 individuals per concentration) and maintained at two temperature regimes, 21.5 °C and 23.5 °C, over a 6-week period. Leaf area was measured weekly, and the remaining bisphenol A concentration was determined. At the end of the experimental period, dry and fresh biomass of the macrophytes were determined gravimetrically. S. auriculata proved more sensitive to the contaminant, particularly at the highest concentration (10 mg/L), exhibiting visible signs of deterioration, including chlorosis and senescence. The higher temperature (23.5 °C) promoted growth and enhanced resistance/resilience to the contaminant in this species. In contrast, R. natans showed deleterious responses to higher temperatures, with negative effects on growth parameters and an apparent reduction in contaminant absorption/adsorption. Thus, under a multi-stressor scenario, S. auriculata may benefit from increased temperature but may be adversely affected by bisphenol A. Conversely, R. natans demonstrated phytoaccumulation potential for bisphenol A but was adversely affected by elevated temperatures.
Effect of multi-stressors (temperature and bisphenol A) on the growth of two macrophyte species
Keywords: multiestressores; macrófitas; mudanças climáticas; bisfenol A; contaminantes emergentes; multi-estressors; macrophytes; climate change; bisphenol A; emerging contaminants; CIENCIAS BIOLOGICAS::ECOLOGIA::ECOLOGIA APLICADA; 14. Vida na Água; 6. Água Potável e Saneamento